Gender and leadership in Africa: Exploring the nexus, trends, and opportunities - Mbo'o-Tchouawou, Michèle; Musembi, Leonard Mulei; Beyene, Hailemichael Taye; Kamau-Rutenberg, Wanjiru (International Food Policy Research Institute, 2019)
The topic of leadership, as a process and a complex set of interactions to motivate and inspire others, has been, in the context of Africa, a matter of interest and research over the past six decades. A study by Fourie, van der Merwe, and van der Merwe (2017) documented some 114 peer-reviewed research articles on leadership in Africa. The articles outline and discuss issues of individual and institutional leadership in the context of politics, gender, traditions and values, religion, education, ideology, and socioeconomic and development dynamics. While the nexus between gender and leadership features as a topical issue in the region, we have known and seen very little evidence about how those topics could be analyzed and addressed beyond the mere application of theories and leadership approaches pertaining to gender (Alimo-Metcalfe 2010; Ayman and Korabik 2010), and particularly to gender equality in Africa.